MANAJEMEN PENDIDIKAN DAYAH BERBASIS KEARIFAN LOKAL UNTUK MENJAGA TRADISI KEISLAMAN DI ACEH - Juniati, Raudhatul (Hijri, 2023)
Dayah, as a traditional Islamic educational institution in Aceh, has played a vital role in shaping character and preserving Islamic traditions in society. However, amidst contemporary challenges and globalization, the management practices of dayah remain under-researched, particularly from the perspective of local wisdom that forms the social foundation of Acehnese communities. This article aims to conceptually analyze how the local wisdom-based educational management of dayah contributes to sustaining Islamic values within Acehnese society. This study employs a qualitative approach using the library research method, focusing on the review of academic literature related to Islamic educational management, Acehnese local wisdom, and the role of dayah. The analysis draws upon books, journals, theses, and relevant documents. The findings indicate that local values such as deliberation (musyawarah), reverence to scholars (ta’zim), communal cooperation (gotong royong), and exemplary leadership are deeply embedded in the dayah management practices. These values significantly contribute to forming an adaptive, sustainable, and culturally rooted educational system. The article concludes that dayah’s local wisdom-based management is not only effective in preserving Islamic traditions but also offers a viable model for Islamic educational development in Indonesia. Hence, integrating modern management systems with indigenous values is essential to support the sustainability of culturally embedded Islamic educational institutions.